Integrated Islamic School Curriculum Analysis Investigated from The Perspective of Students’ Skill in The Industrial Revolution 4.0 Era - Tini, Wulan; Djoehaeni, Heny (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The industrial revolution 4.0 progressively evolves and eventually evokes significant changes within the education field. Advanced technology and information drive the education field towards the digitized direction. The 21st century demands students to possess skills of the 4C’s which scopes the critical thinking, collaboration, communication, and creativity skills. Consequently, the rapid development of science and technology in the 21st century set out the field to more complicated challenges, such as inevitable curriculum changes. Integrated Islamic School Curriculum is the embodiment of scientific and religious knowledge combination as its distinctive characteristic. Simultaneously, the advanced era of the industrial revolution 4.0 requires the curriculum to undertake adjustments. Henceforth, this research strives to discover and analyze the ability of integrated Islamic schools in accommodating challenges and demands of the industrial revolution 4.0 era